Zika Virus Infection and Stillbirths: A Case of Hydrops Fetalis, Hydranencephaly and Fetal Demise - Sarno, Manoel (PLoS Negl Trop Dis, 2016)
BACKGROUND: The rapid spread of Zika virus in the Americas and current outbreak of microcephaly in Brazil has raised attention to the possible deleterious effects that the virus may have on fetuses. METHODOLOGY/PRINCIPAL FINDINGS: We report a case of a 20-year-old pregnant woman who was referred to our service after a large Zika virus outbreak in the city of Salvador, Brazil with an ultrasound examination that showed intrauterine growth retardation of the fetus at the 18(th) gestational week. Ultrasound examinations in the 2(nd) and 3(rd) trimesters demonstrated severe microcephaly, hydranencephaly, intracranial calcifications and destructive lesions of posterior fossa, in addition to hydrothorax, ascites and subcutaneous edema. An induced labor was performed at the 32(nd) gestational week due to fetal demise and delivered a female fetus. ZIKV-specific real-time polymerase chain reaction amplification products were obtained from extracts of cerebral cortex, medulla oblongata and cerebrospinal and amniotic fluid, while extracts of heart, lung, liver, vitreous body of the eye and placenta did not yield detectable products. CONCLUSIONS/SIGNIFICANCE: This case report provides evidence that in addition to microcephaly, there may be a link between Zika virus infection and hydrops fetalis and fetal demise. Given the recent spread of the virus, systematic investigation of spontaneous abortions and stillbirths may be warranted to evaluate the risk that ZIKV infection imparts on these outcomes.